Law Enforcement Operations and Planning with Crime Mapping - Padduyao, Fernando B. (Philippines; Wisemans Books Trading, Inc., 2020)
The author has intended to provide criminology students, who most of them would become police officers, a ready reference of trying to finish a baccalaureate degree in BS Criminology, and hopefully to prepare them to become outstanding uniformed members of the Philippine National Police. He has been teaching police operations to police recruits and he had thought that if only the subject matter is discussed to criminology students, this time, it would be easier for them to understand the topics so that the focus would be on their application.
English Text.
Keywords: Law enforcement